Youtube Videos As Learning Media:A Review In EFL Contexts - Ira Putri Audina; Ni Komang Arie Suwastini; I Gusti Agung Sri Rwa Jayantini; Gede Rasben Dantes; Zulidyana Dwi Rusnalasari (Department of English Language Education, UIN Sunan Ampel Surabaya, 2022)
YouTube has become one of the most visited social media globally. Its saturation in students' lives has triggered experiments and observations on the use of YouTube as learning media. This article discusses the use of YouTube videos to teach English language skills using George's literature review model. The databases for selecting the articles used as the data source in this study were Google scholar and ERIC. The relevant articles were published in reputable international journals and nationally accredited journals in the past ten years. Studies on the use of YouTube videos as a teaching medium indicate that using YouTube videos can improve students' listening, reading, speaking, and writing skills and solve their problems in mastering the skills. Furthermore, YouTube videos have been proven to help students solve their grammar difficulties and increase their vocabulary. YouTube videos are also agreed to have kept the students more interested, motivated, and enthusiastic towards English language learning. These results imply that relevant YouTube videos can provide good learning media for supporting students' learning of English as a Foreign Language.